2012
DOI: 10.1089/jmf.2012.0123
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin Induces Apoptosis and Enhances the Effect of Topotecan on Prostate Cell Line LNCaP

Abstract: C-phycocyanin (C-PC) from Spirulina has been previously shown to have anticancer properties. Here, we report on anticancer activity of C-PC that was isolated from the novel cyanobacterium Limnothrix sp. 37-2-1. C-PC from this organism exhibited anticancer properties in our in vitro systems; however, the required doses were well above the range of anticancer drugs normally used. Therefore, we conducted several experiments to test whether lower-than-usual doses of the anticancer drug topotecan (TPT) can offer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…In contrast to the C-PC of S. platensis, the C-PC from the cyanobacterium Limnothrix sp. exhibited low activity (Gantar et al 2012). When combined with low dose of the anticancer drug topotecan, however, the C-PC from Limnothrix sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the C-PC of S. platensis, the C-PC from the cyanobacterium Limnothrix sp. exhibited low activity (Gantar et al 2012). When combined with low dose of the anticancer drug topotecan, however, the C-PC from Limnothrix sp.…”
Section: Discussionmentioning
confidence: 99%
“…significantly improved the topotecan efficacy. In combination, these two compounds induced apoptosis in the LNCaP (prostate cancer) cells through the generation of ROS and activation of caspases (Gantar et al 2012). The other studied phycocyanins, those of the red algae Porphyra haitanensis (Liu et al 2000a) and P. yezoensis (Zhang et al 2011) significantly inhibited the growth of human leukemia HL-60 cells, and Hep-2 (laryngeal carcinoma) and A375 (malignant melanoma) cell lines, respectively by the unidentified pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-phycocyanin (C-PC) could induce apoptosis on prostate cell line LNCaP. Use of the C-PC-TPT combination can reduce the effective dose of TPT and still maintain its efficacy in inducing significant apoptotic cell death in LNCaP cells (Gantar et al 2012). Anti-inflammatory and c Graph 4 Elston grade of nuclear pleomorphism in the control and treatment groups (mean ± SD).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that as little as a 50 μM dose decreased the proliferation of K562 cells by 49 % for 48 h (Subhashini et al 2004 ). Also, C-PC induced apoptosis in prostate cancer (LNCaP) cell line by diminishing the required dosage of topotecan, an anticancer medication which frequently causes adverse side reactions in patients (Gantar et al 2012 ). In another study involving human hepatoma cell line (HepG2), C-PC led to a reduction in the proliferation of the cells with the highest reduction observed at a concentration of 7 μg/ml C-PC along with a loss of nuclear entities due to fragmentation (Basha et al 2008 ).…”
Section: As Anticancer Agentsmentioning
confidence: 99%